Tideglusib-loaded chitosan-incorporated bacterial cellulose hydrogel for enhanced palatal wound healing - Odabas, Elif Var; Unal, Semra; Alemdag, Berna; Gunduz, Oguzhan; Tekkesin, Merva Soluk; Turet, Deniz Mukaddes; Kuru, Leyla; Agrali, Omer Birkan (ELSEVIER, 2026)
Bacterial cellulose (BC) has been investigated for use as a wound dressing owing to its interconnected porosity structure and biocompatibility, which support tissue formation and cell interactions. Periodontal wounds left to heal secondarily after periodontal graft surgery may cause discomfort, pain, and delayed tissue repair, depending on the patient's condition. Topical application of antimicrobial treatment is recommended to avoid these problems after surgery. The purpose of this research is to investigate the influence of tideglusib (Td) when administered topically using a chitosan-incorporated BC-based hydrogel carrier on the early healing of palatal wounds in rats. The animals were randomly allocated to four groups at the commencement of the trial. Seven animals were immediately euthanized and constituted the initial group. The remaining 21 animals were split up randomly into three groups: control group, hydrogel group, and Td + Hydrogel group. The wound surface area was evaluated using photographic techniques, whereas the epithelialization rate was determined by histological investigation at seven days post-surgery. Axin2 and type I collagen expressions were assessed immunohistochemically. Statistically significant changes were identified in wound surface area and distance between epithelial borders in intergroup comparisons. Pairwise comparisons demonstrated significant differences between the baseline and Td + Hydrogel groups only. Topical use of chitosan incorporated BC-based hydrogel loaded with Td suggested a beneficial impact on the healing of palatal mucosal wounds in rats.
Keywords: Palatal mucosal wound healing; Tideglusib; Wnt signaling pathway; BETA-CATENIN; ORAL-MUCOSA; RAT; SKIN; LOCALIZATION; SCAFFOLDS; TISSUES; GROWTH; AGENTS; Biochemistry & Molecular Biology; Chemistry; Polymer Science